Formulation of a 3-months Stability Oral Viscous Budesonide Gel and Development of an Indicating Stability HPLC Method - Bonnet Mathilde; Dermu Marine; Roessle Clara; Bellaiche Marc; Abarou Tarik; Vasseur Véronique; Benakouche Samira; Storme Thomas (De Gruyter, 2018)
Eosinophilic Esophagitis is an increasing pathology which can cause stomach symptom like dysphagia, vomiting, food blockage. The treatment consists in dietary therapy and topical corticosteroid therapy to avoid the important number of side effects of the oral corticosteroids. There is presently no available topical form adapted for treating esophageal pathology.